Pengujian Niat Mahasiswa Untuk Mengikuti Ujian Sertifikasi Keahlian Akuntansi Dasar (USKAD) - Yanto Darmawan; Rahimah Rahimah (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this research is analyzing factor that influence the intention of diploma degree student in accounting to take uskad exam. Three construct of theory planned behavior ( attitude toward behaviour, subjective Norm and perceived behavioural controll) were used as basic model for this research. Data were taken by using questioners from 199 student of politeknik YKPN Yogyakarta and then analyzed by structtural quation modeling - partial least square using smart PLS 4.0. The result of the analysis concludes that three construct of theory of planned behavior positively influence the student's invention to take uskad exam.